Vitrimer-like shape memory polymers : characterization and applications in reshaping and manufacturing - Wang, Tao Xi (2021)
The shape memory effect (SME) refers to the ability of a material to recover its original shape, but only in the presence of a right stimulus. Most polymers, either thermo-plastic or thermoset, can have the SME, although the actual shape memory performance varies according to the exact material and how the material is processed. Vitrimer, which is between thermoset and thermo-plastic, is featured by the reversible cross-linking. Vitrimer-like shape memory polymers (SMPs) combine the vitrimer-like behavior (associated with dissociative covalent adaptable networks) and SME, and can be utilized to achieve many novel functions that are difficult to be realized by conventional polymers. In the first part of this paper, a commercial polymer is used to demonstrate how to characterize the vitrimer-like behavior based on the heating-responsive SME. In the second part, a series of cases are presented to reveal the potential applications of vitrimer-like SMPs and their composites. It is concluded that the vitrimer-like feature not only enables many new ways in reshaping polymers, but also can bring forward new approaches in manufacturing, such as, rapid 3D printing in solid state on space/air/sea missions.